The Construction of Criminal Liability of the National Land Agency in the Issuance of Duplicate Certificates - Satriadi; Pujiyono; Elfia Farida (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2026)
This study analyzes the construction of criminal liability for the National Land Agency (BPN) regarding the chronic issue of double land certificates in Indonesia. The central problem is the weak criminal law enforcement against BPN or its officials, as these cases are predominantly resolved only through administrative (PTUN) or civil channels. Using normative legal research with statutory and conceptual approaches, this study examines criminal law norms and liability doctrines. The analysis focuses on applying vicarious liability and identification theories to determine the extent to which BPN or its officials can be held criminally responsible for public losses. The results reveal that constructing BPN’s criminal liability is hindered by a lack of regulatory synchronization between administrative and criminal law. There is a tendency to separate personal faults of officials (fautes personelles) from organizational faults (fautes de service), which often obscures criminal liability in cases of land mafia or fatal negligence. In conclusion, this study emphasizes the urgency of strengthening BPN's criminal accountability as part of bureaucratic and agrarian reform. This is crucial to create a deterrent effect for internal actors, ensure land data integrity, and provide substantial legal protection for land rights holders.